Enzymatically crosslinked Tyramine-Gellan gum hydrogels as drug delivery system for rheumatoid arthritis treatment - Oliveira, Isabel Maria Lopes Matos (2021)
Rheumatoid arthritis (RA) is a chronic inflammatory disease characterized by joint synovial inflammation, as well as cartilage and bone tissue destruction. Current strategies for the treatment of RA can reduce joint inflammation, but the treatment options still represent stability concerns since they are not sufficient and present a fast clearing. Thus, several drug delivery systems (DDS) have been advanced to tackle this limitation. Injectable gellan gum (GG) hydrogels, reduced by physical crosslinking methods, also being proposed as DDS, but this kind of crosslinking can produce hydrogels that become weaker in physiological conditions. Nevertheless, enzymatic crosslinking emerged as an alternative to increase mechanical strength, which can be adjusted by the degree of enzymatic crosslinking. In this study, tyramine-modified gellan gum (Ty-GG) hydrogels were developed via horseradish peroxidase (HRP) crosslinking; and betamethasone was encapsulated within, to increase the specificity and safety in the treatment of patients with RA. Physicochemical results showed that it was possible to modify GG with tyramine, with a degree of substitution of approximately 30%. They showed high mechanical strength and resistance, presenting a controlled betamethasone release profile over time. Ty-GG hydrogels also exhibited no cytotoxic effects and do not negatively affected the metabolic activity and proliferation of chondrogenic primary cells. Furthermore, the main goal was achieved since betamethasone-loaded Ty-GG hydrogels demonstrated to have a more effective therapeutic effect when compared with the administration of betamethasone alone. Therefore, the developed Ty-GG hydrogels represent a promising DDS and a reliable alternative to traditional treatments in patients with RA